A structured multi-stakeholder learning process for Sustainable Land Management - Schwilch, Gudrun (2019)
There are many, often competing, options for Sustainable Land Management (SLM). Each must be assessed - and sometimes negotiated - prior to implementation. Participatory, multi-stakeholder approaches to identification and selection of SLM options are increasingly popular, often motivated by social learning and empowerment goals. Yet there are few practical tools for facilitating processes in which land managers may share, select, and decide on the most appropriate SLM options. The research presented here aims to close the gap between the theory and the practice of stakeholder participation/learning in SLM decision-making processes. The paper describes a three-part participatory methodology for selecting SLM options that was tested in 14 desertification-prone study sites within the EU-DESIRE project. Cross-site analysis and in-depth evaluation of the Moroccan and Portuguese sites were used to evaluate how well the proposed process facilitated stakeholder learning and selection of appropriate SLM options for local implementation. The structured nature of the process - starting with SLM goal setting - was found to facilitate mutual understanding and collaboration between stakeholders. The deliberation process led to a high degree of consensus over the outcome and, though not an initial aim, it fostered social learning in many cases. This solution-oriented methodology is applicable in a wide range of contexts and may be implemented with limited time and resources.